Health promotion and prevention of chronic non-communicable diseases in the context of the COVID-19 pandemic. Consensus of experts of the National society of evidence-based pharmacotherapy and the Russian society of the prevention of non-communicable diseases - O. M. Drapkina; M. G. Gambaryan; B. E. Gorny; N. S. Karamnova; A. V. Kontsevaya; N. K. Novikova; M. V. Popovich; I. A. Rybakov; A. M. Kalinina (Кардиоваскулярная терапия и профилактика, 2020)
.